Rhino-orbito-cerebral mucormycosis after allogeneic hematopoietic stem cell transplantation for very severe aplastic anemia in a child: a case report - Ma, Yimei; Xia, Ziting; Cheng, Bochao; Wang, Bo; Huang, Xingming; Lu, Xiaoxi (Frontiers in Pediatrics, 2025)
Rhino-orbito-cerebral mucormycosis (ROCM) is a rare and life-threatening fungal infection that predominantly affects immunocompromised individuals, such as those undergoing hematopoietic stem cell transplantation (HSCT). This report describes the case of a 10-year-old girl with very severe aplastic anemia (VSAA) who underwent an haploidentical HSCT from her father. She initially achieved successful engraftment with a donor chimerism rate of 98.25% on day 60. However, on day 65 post-transplant, she developed severe right-eye pain, progressive swelling, and visual impairment. Comprehensive evaluations, including contrast-enhanced magnetic resonance imaging (MRI) and cerebrospinal fluid (CSF) analysis, revealed extensive orbital and cerebral involvement consistent with ROCM. Intensive antifungal therapy with liposomal amphotericin B and posaconazole, along with endoscopic surgical debridement of the infected sinuses and orbital regions, was initiated. Post-treatment MRI scans demonstrated a significant reduction in cerebral edema and other abnormalities, while repeated CSF analyses confirmed the absence of fungal elements. This case underscores the critical need for early diagnosis and aggressive management of ROCM in immunocompromised patients, particularly following HSCT.